FENOMENAJILBAB DALAM KARYA DIGITAL IMAGING - Drs. Wisdiarman, M.Pd., BOY SANDI, Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2017)
Clothes is the humans primary, Islam has the dress code to the members of the religion community, especially the moeslimah. The headgear is obligatory for muslimah, today the veil becomes trend for women that appropriate with the law of islam as the rules had fade away from islam properly. The purpose of this creation is to visualize the phenomenon jilbab that occurred in society in the work of â€œDigital Imagingâ€. Such as : (1). POP (2). Modernisasi (3). Transisi (4). Follower (5). Moving On (6). Kontradiksi 1 (7). Kontradiksi 2 (8).Terbingkai (9). WOW (10). Fenomena.Kata Kunci : Phenomenon Jilbab, Digital Imaging